Ontogeny of reactive nitrogen species production by blood phagocytes in pigs - Ondráčková, Petra; Faldyna, Martin; Kovářů, Hana; Kovářů, František; Ondráček, Jaroslav (Physiological research, 2008)
The aim of this work was to evaluate ontogeny of reactive nitrogen species (RNS) production by peripheral blood phagocytes in pig. Pig fetuses (55 and 92 days of gestation) and postnatal piglets (1, 3, 8, 17, 31 and 41 days after birth) were used. RNS production was measured by fluorescent probes diaminofluorescein-diacetate (DAF-FMDA) and dichloro-fluorescein-diacetate (H2DCFDA). Levels of nitration of cell proteins were established by immunofluorescent detection of nitrotyrosine. Levels of plasma nitrites/nitrates were detected spectrophotometrically by Griess reaction. Nitric oxide production measured by DAF-FMDA in neutrophils decreased during postnatal life. Spontaneous RNS measured by H2DCFDA decreased from 55th day of gestation to the 41st day of life. Phorbol-12-myristate-13-acetate activated production decreased during postnatal life. Production of NO measured by DAF-FMDA in macrophages decreased from the first to 41st day after birth. RNS production measured by H2DCFDA in monocytes did not show any significant changes during ontogeny. The level of nitrotyrosine significantly decreased from the third to 17th day. Levels of plasma nitrites/nitrates gradually decreased from the 55th day of gestation to the 41st day after birth. A temporary increase in all parameters occurred after weaning, but without any significance. In conclusion, RNS production has a decreasing trend during ontogeny and is transiently upregulated after weaning.
Keywords: fagocyty; Longitudinal Studies; Sus scrofa; reaktivní formy dusíku; novorozená zvířata; oxid dusnatý; stárnutí; odstavení; zvířata; Reactive Nitrogen Species; Nitric Oxide; Aging; vývoj plodu; Animals, Newborn; Phagocytes; longitudinální studie; Fetal Development; Animals; Weaning